2021
DOI: 10.1155/2021/1907914
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fish Collagen-Nanochitosan-Henna Extract Composites for the Control of Skin Pathogens and Accelerating Wound Healing

Abstract: Skin is the largest protective organ that could be recurrently wounded and attacked by microorganisms. The wounded skin safeguarding and supporting were intended through natural derivatives. Fish collagen (Cg) type I, extracted from sea bream (Spondyliosoma cantharus), chitosan nanoparticles (NCht) from shrimp shells, and henna (Lawsonia inermis L.) leaves extract (He) were produced and physiochemically characterized. The antimicrobial potentialities of these compounds and their composites were assessed toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…Propolis-CMPs inhibited biofilm formation and improved eradication of preformed biofilm in E. faecalis [142], melatonin loaded in chitosan/poloxamer NPs demonstrated antibiofilm activity against S. aureus. The methicillin-resistant S. aureus (MRSA) [143], essential oil of Homalomena pineodora in CNPs, generated greater inhibition zones in a range of Grampositive and Gram-negative bacteria as well as yeasts [144], and CNPs with Henna extract improved antimicrobial activity against S. aureus and C. albicans [145].…”
Section: Particles and Carriersmentioning
confidence: 99%
“…Propolis-CMPs inhibited biofilm formation and improved eradication of preformed biofilm in E. faecalis [142], melatonin loaded in chitosan/poloxamer NPs demonstrated antibiofilm activity against S. aureus. The methicillin-resistant S. aureus (MRSA) [143], essential oil of Homalomena pineodora in CNPs, generated greater inhibition zones in a range of Grampositive and Gram-negative bacteria as well as yeasts [144], and CNPs with Henna extract improved antimicrobial activity against S. aureus and C. albicans [145].…”
Section: Particles and Carriersmentioning
confidence: 99%
“…Topical antibiotics are used for managing of burn/wound; however, finding new medication with higher efficacy and lower side effects is still considered as a priority (Dwivedi et al 2017;Tayel et al 2021). Umachigi et al (2008) reported that wound healing and repair was enhanced by applying QIE, e.g.…”
Section: Wound Burn Healing Activities Of Qie and Molecular Dockingmentioning
confidence: 99%
“…The skin being the largest body organ, it plays several vital roles, such as protection, thermoregulation, secretory and sensory activities (Njoroge and Bussmann 2007;Tayel et al 2021). Therefore, topical wounds and skin infections require great attention to prevent secondary complications caused by microbial invasion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen molecules become more positively charged in acidic environments, and this positive charge helps their solubilization by producing repulsion among tropocollagen molecules. [17] Organic acids, including i) acetic acid (CH3COOH) [20,21], ii) citric acid (C6H8O7) [22], iii) tartaric acid (C4H6O6) and iv) chloroacetic acid and inorganic acids such as i) hydrochloric acid (HCl) and ii) formic acid (CH2O2), are used for the isolation of collagen. [4] Organic acids, on the other hand, are more successful than inorganic acids at cleaving the crosslinks of collagen molecules, resulting in better collagen extractability.…”
Section: Chemical Hydrolysismentioning
confidence: 99%